Preserving rumah tiang 12, Kelantan through digital informative interactive exhibition: mutia kita - Wan Zulkifli, Wan Noor Syahira; Ab Jalil, Nurlelawati; Mohd. Din, Shamzani Affendy (Kulliyyah of Architecture & Environmental Design, 2024)
"Mutia Kita" is a project dedicated to the digital preservation and presentation of traditional Malay houses, aiming to raise awareness of their cultural and architectural significance. This initiative highlights the importance of safeguarding these heritage structures by creating an interactive digital exhibition designed to engage the community, particularly younger generations. The primary objective of the project is to educate the public on the role traditional Malay houses play in expressing and preserving the identity of Malay culture. By digitising and presenting these houses in an accessible and engaging format, the exhibition offers a deeper understanding of their historical, architectural, and cultural value. The qualitative research methodology adopted includes interviews and case studies of traditional Malay House : Rumah Tiang 12 in Kelantan, which provide valuable insights into these houses' unique features and history. The final product, developed using PowerPoint, serves as an interactive platform where visitors can explore the houses’ unique design, context, and conservation efforts digitally. Through this approach, the project is not only accessible to all but can inspire appreciation for traditional Malay houses and foster a collective commitment to their preservation for future generations.